Tunable elastic heterogeneity caused by deformation-induced magnetization in flexible metallic glass. (15th March 2017) - Huang, B.; He, Q.F.; Wang, A.D.; Zhao, C.L.; Wang, Q.; Yang, Y.; Liu, C.T.
Abstract: In this letter we explore the magnetization effect on mechanical properties of a ductile Fe83 C1 B11 Si2 P3 metallic glass (MG). We firstly demonstrate that magnetic anisotropy can be systematically created by plastic deformation using high-load Berkovich indentation, and then provide compelling evidence by subsequent spherical nanoindentation which reveals tunable magnetization-induced submicron elastic heterogeneity. A new mechanism of magnetomechanical interaction, different from the alteration of "flow defect", is proposed for explaining the apparent softening in the region without plastic deformation. Our studies have significance for modification and controlling of the microstructure and mechanical properties of MGs with respect to magnetic effect. Graphical abstract: